Explicit/implicit multi-time step co-simulation in unbounded medium with Rayleigh damping and application for wave barrier. Issue 14 (5th December 2020) - Li, Sijia; Brun, Michael; Djeran-Maigre, Irini; Kuznetsov, Sergey
Abstract: Co-simulation strategies using both Abaqus/Explicit and Abaqus/Implicit are investigated for analysing wave propagation in two-dimensional unbounded soil domain. The co-simulation is based on the coupling GC method, allowing for coupling different finite element codes with different time integrators and time-scales depending on the partitions of the domain. Absorbing layers using increasing damping (ALID), based on Rayleigh viscous damping, are considered at the boundary to model the semi-infinite medium. The proposed absorbing region is called hybrid (different time integrators) asynchronous (different time steps) absorbing layers using increasing damping (HA-ALID). Lamb's test and a wave barrier problem are investigated. First, HA-ALID turns out to be more accurate than non-reflective conditions available in Abaqus/Explicit. Second, the critical time step in the domain of interest remains unaffected by the choice of damping characteristics in the HA-ALID, contrary to the case of a full explicit computation. Third, the time steps for the solid barrier and the HA-ALID are not restrained by the CFL condition imposed by the explicit partition for stability reasons. Because of its good accuracy and ability to be realized using only FE Abaqus package, without a third-party software component, this strategy provides a wide range of applications in soil–structure interaction problems.